Does the duration of gonadotropin stimulation affect embryo quality on post-retrieval day 3? - YOLDEMİR, AHMET TEVFİK (INFORMA HEALTHCARE, 2011)
Aim. To determine if the duration of ovarian hyperstimulation affects quality of embryos on the 3rd day. Methods. Retrospective cohort study was designed in a University affliated hospital. Six-hundred fifteen women undergoing first IVF treatment were grouped according to the duration of controlled ovarian hyperstimulation (COH) in long-down regulated cycles. Group A consisted of women with 8 or less days of COH, Group B consisted of women who had between 9 and 10 days of COH and Group C had 11days or more COH. The degree of fragmentation and asymmetry of blastomeres were compared for the 3rd day after oocyte retrieval. Results. On day 3, there were more embryos with 10-25% fragmentation in Group A than in Group B. Embryos were also less symmetrical in Group A than in Group B. Conclusions. COH cycles which are shorter than 9 days result in more embryos with more than 10% fragmentation on post-retrieval day 3.
Keywords: Gonadotropin; duration of stimulation; embryo quality; assisted reproductive techniques; INTRACYTOPLASMIC SPERM INJECTION; IN-VITRO FERTILIZATION; POLAR BODY MORPHOLOGY; OOCYTE MORPHOLOGY; IMPLANTATION; PREGNANCY; PROBABILITY; FOLLICLE; FRAGMENTATION; MATURATION